Infratemporal fossa approach type a with transcondylar‐transtubercular extension for Fisch type C2 to C4 tympanojugular paragangliomas. Issue 11 (18th November 2013) - Sanna, Mario; Shin, Seung‐Ho; Piazza, Paolo; Pasanisi, Enrico; Vitullo, Francesca; Di Lella, Filippo; Bacciu, Andrea
Abstract Background The classic infratemporal fossa type A approach (IFTA‐A) permits superior and anterior exposure of the jugular foramen. The transcondylar‐transtubercular extension facilitates posteroinferior and medial access to the jugular foramen. The purpose of this study was to present the IFTA‐A with transcondylar‐transtubercular extension and to assess its surgical results. Methods A review of patients with tympanojugular paraganglioma who underwent resection through the IFTA‐A with transcondylar‐transtubercular extension was performed. Results In all, 39 patients were included in the study. The average follow‐up was 23.6 months. Gross total tumor removal was achieved in 87.2% of the cases and there was evidence of recurrence in 5.9% of this group. Conclusion The transcondylar‐transtubercular extension of the classic IFTA‐A is aimed at making the excision of Fisch type C2 to C4 tympanojugular paragangliomas simpler and safer by drilling out one third of the lateral part of the occipital condyle and removing the jugular process and jugular tubercle. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1581–1588, 2014